Wire arc additive manufacturing of functionally graded material with SS 316L and IN625: Microstructural and mechanical perspectives. (August 2022) - Sasikumar, R.; Kannan, A. Rajesh; Kumar, S. Mohan; Pramod, R.; Kumar, N. Pravin; Shanmugam, N. Siva; Palguna, Yasam; Sivankalai, Sakthivel
Abstract: In the present study, functionally graded material (FGM) of Austenitic Stainless Steel-SS 316L and Nickel-based superalloy-Inconel 625 (IN625) was manufactured via Gas Metal Arc Welding (GMAW) based Wire Arc Additive Manufacturing (WAAM). WAAM processed FGM was well-formed without any defects and solidification cracking was not observed at the bi-metallic interface (IF) region. Microstructural features show a sharp transition at the IF with a discontinued dendritic structure. Energy-dispersive X-ray spectroscopy (EDS) examination confirmed the fine dissolution of elements at the IF and no major difference in the composition was observed. Electron Backscatter Diffraction (EBSD) maps confirmed that the grains are dominantly columnar while the IF revealed the smooth crystallographic growth along with large elongated dendrites in the< 001 >direction. The microstructure was mainly austenitic in the SS 316L layers with a lower fraction of ferrite while precipitates were noticed in the IN625 layers within the austenitic matrix. Yield strength (YS) and tensile strength (UTS) of SS 316L and IN625 were comparable with wrought ones. All the IF samples at 90° failed in the SS 316L region because of the lower UTS in comparison to IN625 and the mode of fracture was ductile. Microhardness measurements depicted the gradual change of hardness along the building direction. The present work highlights the potential of WAAM to fabricate FGM with required properties and is a viable manufacturing alternative to the traditional manufacturing techniques for producingFGM's. Graphical Abstract: ga1